The Effect of Marketing Mix and Service Quality on Satisfaction and Revisit Intention to Kampung Coklat, Blitar Regency - Dethan, Antonietta Gizela; Suryawardani, I Gusti Ayu Oka; Wiranatha, Agung Suryawan (E-Journal of Tourism; Volume 7 Number 2 (September 2020), 2020)
Marketing mix and service quality are two important aspects that need to be considered by a tourist attraction in order to provide satisfaction to tourists. Tourist satisfaction can be achieved if the products sold are supported by good quality and price of products and services. Satisfaction can also affect the intention of tourists to revisit these tourist attractions. The problem that occurs in educational tourism in Kampung Coklat, Blitar Regency is that some tourists are not satisfied with the elements of the marketing mix and the quality of the services offered. This study aims to analyze the effect of marketing mix and service quality on tourist satisfaction in Kampung Coklat, Blitar Regency, to analyze the effect of marketing mix and service quality on revisit intention to Kampung Coklat, Blitar Regency and to analyze the effect of tourist satisfaction on revisit intention to Kampung Coklat, Blitar Regency. The number of respondents in this study were 100 people who were chosen deliberately with the criteria being at least 17 years old and visiting Kampung Coklat for the first time. The analysis was performed using Structural Equation Modeling (SEM) through the SmartPLS version 3.0 application. The results showed that marketing mix and service quality had a significant effect on tourist satisfaction, marketing mix and service quality had a significant effect on revisit intention, and tourist satisfaction had a significant effect on revisit intention. Keywords: Marketing Mix, Service Quality, Satisfaction, Revisit Intention